Faire carrière à Paris : Armand Bloch (1866-1932) et la Franche-Comté, l’importance du soutien régional pour les artistes au xixe siècle - Clémentine Delplancq (Les Cahiers de l'École du Louvre)
How is an artistic career built? There are many possible answers; here, we examine that of regional affiliation, through the case study of the sculptor Armand Bloch (1866–1932). A wood carver and the maker of several public monuments, he benefitted throughout his life from the advantages of his native region, Franche-Comté. The vast network formed by Franche-Comté natives in Paris included artists, senior civil servants and politicians, and was devoted to the success of the natives of the region. Thanks to these relations, and particular to the resulting associations and societies, Bloch received subsides and especially commissions that allowed him to practise his art, exhibit his work and support himself. The study of the various workings of regional mutual aid sheds new light on the working conditions of sculptors.